Effects of Strategic Partnerships in Building Organizational Capacity in the Oil Extractive Industry in Kenya: A Case of National Oil Corporation - Minja, Prof. David; Waweru, Lillian (European Journal of Business and Strategic Management, 2016)
Purpose: This study sought to evaluate the effects strategic partnerships have on building capacity of firms in oil and gas industry in the emerging frontier. Theory and practice suggest that firms with low capacity to exploit oil and gas can venture into strategic alliances with well established firms to enable them acquire skills, competences and capital required to develop their capacity. The theory guiding this study was the Resource Based View of the firm. The objectives of this study were: To establish whether strategic partnerships were being used by National Oil Corporation of Kenya to develop its oil and gas extractive capacity; To examine the impact of strategic partnerships in building organizational capabilities; and to identify any practical lessons that could guide other oil and gas emerging frontiers. Methodology: The research adopted a descriptive study and used a case study which was essential for acquiring in- depth information that was required for this study. The target population was the employees of the company working in the Upstream Department who were picked using a simple random sampling technique. Results: The study found out that strategic partnerships had an impact on brand visibility and growth, enhancing financial capacity, technological capacity and enabling knowledge transfer. Contribution to practice and policy recommendation: The study concludes that emerging oil and gas frontiers should adopt strategic partnerships to build their capacity.